Vascularized Hypothenar Fat Pad Flap in Revision Surgery for Carpal Tunnel Syndrome - Wichelhaus, Alice; Mittlmeier, Thomas; Gierer, Philip; Beck, Markus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objective To evaluate the results of the hypothenar fat pad flap in revision surgery for carpal tunnel syndrome (CTS).Patients and methods We retrospectively analyzed 18 consecutive patients (14 women, 4 men) who had recurrent CTS. The average age was 61 years. All patients had undergone the index carpal tunnel release 5 to 22 months ago. From November 2009 to November 2013, they were treated by decompression of the median nerve and a vascularized hypothenar fat pad flap. The intraoperative findings were assessed as well as the level of pain, recovery of sensory and motor dysfunction, Hoffmann-Tinel sign, nerve conduction studies, grip and pinch strength, and Disability of Hand and Shoulder Questionnaire (DASH) score. All patients were reevaluated at an average of 22 months after revision surgery.Results After revision surgery, 15 patients reported symptomatic improvement. No patient reported worsening of symptoms. A median DASH score of 18 was reached. Grip strength recovered to 90% of the contralateral side. Overall, 15 patients were satisfied with the result of the operation; 3 did not cope with pain and dysfunction. Recurrence was not found in any case.Conclusion The hypothenar fat pad flap can be used successfully as an adjunct to microsurgical neurolysis for the treatment of recurrent CTS secondary to perineural scarring, although a functional deficit remains in some patients.
Keywords: recurrent carpal tunnel syndrome; revision surgery; hypothenar fat pad flap